2012
DOI: 10.1111/j.1600-9657.2011.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

History of the Dental Trauma Guide

Abstract: -The history of the Dental Trauma Guide dates back to 1965, where guidelines were developed for trauma records and treatment of various trauma entities at the Department of Oral and Maxillofacial Surgery at the University Hospital in Copenhagen. In 1972, a unique possibility came up at the Serum Institute in Copenhagen to test various dental trauma procedures in monkeys, which served as kidney donors in the polio vaccine production. Over the years, 40 000 dental trauma patients were treated at the Trauma Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 118 publications
(166 reference statements)
1
11
0
Order By: Relevance
“…The most common injury type of the present study was injury to gingivae and oral mucosa (26.9%), in contrast to periodontal tissue injuries (51.8%) in a study on traumatic dental injuries in a teaching hospital in Wuhan, China while under transmission control measures during the COVID-19 epidemic between 23 January and 7 April 2020 [23]. The findings of both studies are comparable as they used the same dental trauma classification of Andreason [26]. Moreover, the findings of the present study revealed that the majority of patients (82.4%) had sustained injuries due to falls which had occurred at their homes and its surroundings.…”
Section: Discussionsupporting
confidence: 61%
“…The most common injury type of the present study was injury to gingivae and oral mucosa (26.9%), in contrast to periodontal tissue injuries (51.8%) in a study on traumatic dental injuries in a teaching hospital in Wuhan, China while under transmission control measures during the COVID-19 epidemic between 23 January and 7 April 2020 [23]. The findings of both studies are comparable as they used the same dental trauma classification of Andreason [26]. Moreover, the findings of the present study revealed that the majority of patients (82.4%) had sustained injuries due to falls which had occurred at their homes and its surroundings.…”
Section: Discussionsupporting
confidence: 61%
“…For 40 years, patient records have been collected at the University Hospital in Copenhagen, creating the information contained in the extensive database used in developing the Dental Trauma Guide for prognosis estimation. Since 1965, standardized documentation of trauma treatments has been collected, and this large material (4000 cases) together with the results of 79 clinical studies and 65 experimental animal studies using monkeys now forms the scientific basis for the Dental Trauma Guide (7) (Fig. 1).…”
Section: How Big Is the Knowledge Gap Before We Can Have The Necessarmentioning
confidence: 99%
“…They allow the researchers to control the parameters that may influence the outcome of the experiment in a fashion not attainable in human studies as the injuries can be inflicted by the examiner under controlled conditions (6). The current treatment guidelines give testimony to the value of animal studies as they rely heavily on information obtained from animal studies (7).…”
Section: What Is the Cause Of This Problem?mentioning
confidence: 99%
“… 1 Specific population studies have shown that trauma to the oral region can account for 5% of all injuries, with the highest risk in children aged 0 to 12 years. 2 Guidelines for the management of traumatized teeth have been clearly outlined 3 ; however, despite the dentist's best effort, tooth loss following trauma is sometimes inevitable. In order to select the best treatment option for patients with a lost anterior tooth, the clinician must consider several factors such as the patient's growth status, success rates and costs of various treatment options, patient preferences, and, most importantly, treatment options that will enable long-term rehabilitation.…”
Section: Introductionmentioning
confidence: 99%